Religious Coping, Social Support and Subjective Severity as Predictors of Posttraumatic Growth in People Affected by the Earthquake in Chile on 27/2/2010 - Felipe E. García; Darío Páez; Giordana Zurtia; Héctor Martel; Alejandro Reyes‐Reyes (2014)
The aim of this research is to study the impact of religious coping, social support and subjective severity on Posttraumatic Growth (PTG) in people who lost their homes after the earthquake in Chile in 2010 and who now live in transitional shelters. One hundred sixteen adult men and women were evaluated using a subjective severity scale, the Posttraumatic Growth Inventory (PTGI), the Multidimensional Scale of Perceived Social Support (MSPSS) scale of social support and the Brief RCOPE scale of religious coping. The multiple linear regression analysis shows that social support and positive religious coping have an impact on PTG. On using a bootstrap estimate, it was found that positive religious coping fully mediates the relationship between subjective severity and PTG.